(untitled) (Studia Prawnicze / The Legal Studies, 2016)
Faktem jest, że polski system prawny pozwala każdemu, kto posiada pełną zdolność do czynności prawnych, rozrządzić własnym majątkiem na wypadek śmierci. Jak wskazuje art. 941 Kodeksu cywilnego, można tego dokonać wyłącznie przez testament. Jest on jedyną czynnością prawną, na podstawie której może zostać powołany spadkobierca. Spadkodawcy, w celu rozdysponowania dorobku według własnego uznania, decydują się właśnie na to rozwiązanie, gdyż ustawowy porządek dziedziczenia uwzględnia jedynie typowe sytuacje. W ten sposób realizowana jest jedna z funkcji testamentu, czyli dostosowanie rozrządzeń majątkiem spadkowym do sytuacji rodzinnej spadkodawcy. Do rozrządzeń testamentowych, których dotyczy swoboda testowania, zalicza się: ustanowienie spadkobiercy, powołanie wykonawcy testamentu, ustanowienie zapisu, polecenia, fundacji, a także wykluczenie od dziedziczenia i wydziedziczenie. Jednak, aby rozrządzenie ostatniej woli było ważne i niepodważalne, muszą być spełnione określone przesłanki. Nie może być ono dokonane w dowolny sposób. Polskie prawo precyzuje i określa wymogi formalne, bez spełnienia których testament będzie nieważny. Testator wishing to dispose of assets through a testament has a choice of several forms of testament: ordinary and special. Preparing the act of last will it’s necessary to observe the formal requirements set forth by law, otherwise this will is going to be invalid. The existing provisions about the form don’t fully meet the objectives for which they were introduced. Approved forms of will raise a number of concerns, and the regulations governing them require immediate correction. The provisions of the form can be accused of: imprecision, inconsistency, and in some cases the lack of practicality and the lack of adaptation to contemporary needs and opportunities. But above all, unfortunately, they often interfere with the will of the testator. That formalism in practice often thwarts the will of the testator. The rules, which were supposed to protect and make its fulfillment often become an obstacle. Formal requirements introduced, among others, due to the reduction of falsifying wills is not fully recognized. There are necessary changes in regulations concerning the form of the disposition mortis causa. The existing forms of the testament need modifications and some of them total removal. There is a need also to create new types of wills. However, the most important is to enable the maintenance of the statement in force, in the case that the testament is authentic and the testator made it consciously leaving out some requirement of form.